Observational assessment of the utilization of donated point of care tests and glycemic control at free and charitable clinics across the United States - Sonak D. Pastakia; Heidi Schutz; Tena Tiruneh; Ariana Gordillo De Vivero; Lindsey Dodds (Practical Laboratory Medicine)
Introduction: Populations experiencing poverty often lack access to convenient lab tests. This analysis assesses trends observed from a national point of care (POC) lab donation program for free and charitable clinics across the United States. Methods: A total of 16 clinics were selected to receive a comprehensive package of POC lab tests. De-identified data on POC test utilization and results were assessed to descriptively identify trends in utilization (primary objective) and glycemic control (secondary objective). A paired t-test was utilized to identify statistically significant changes in HbA1c from baseline to predefined 90-day time intervals for all people living with diabetes (PLWD) and those with a baseline HbA1c ≥ 9.0 % (75 mmol/mol). The main comparison of interest was the change in HbA1c from baseline to 90–179 days. Results: A total of 17,563 POC tests were completed for 9658 patients with 3223 tests being HbA1c’s. In the secondary analysis of PLWD with a baseline HbA1c ≥ 9.0 % (75 mmol/mol), patients who completed an HbA1c between 90 and 179 days (n = 188) demonstrated a statistically significant mean reduction from baseline of -1.2 % (95 % CI, -1.6 % to −0.9 %, p < 0.01, -10 mmol/mol [95 % CI, -6 mmol/mol - -14 mmol/mol]). Discussion: The provision of POC labs helped support the care populations experiencing poverty received at free and charitable clinics, especially for chronic diseases like diabetes.